Representasi Wanita Dalam Media Massa Masa Kini - Watie, Errika Dwi Setya (Jurnal The Messenger, 2010)
Media audience, in general, using representation of women in the media to "see" women. How does the media show the figure of a woman often becomes references and examples used to assess women in general. Not only how man seeing woman, but women see themselves and other women see each other. This condition seemed to reinforce the encouragement of women to remain in the view of women in the past is loaded with socio-political. In many media, women are still portrayed as "mere body" related to sexuality. Besides the still dominant view that shows women as "a figure in the kitchen", the less equilibrate view that showing women in the intellectual and career figures, reinforce the representation of "traditional" women. And finally appeared in public perception will remain the same. Representation of woman according to the spirit of emancipation of women only appears in the commemoration of Kartini day, mothers day, and other momentum associated with women.